Tuning of multiple luminescence outputs and white-light emission from a single gelator molecule through an ESIPT coupled AIEE process - Maity, Arunava; Ali, Firoj; Agarwalla, Hridesh; Anothumakkool, Bihag; Das, Amitava (Chemical Communications, 2015)
A unique example of an ESIPT coupled AIEE process, associated with a single molecule (1), is utilized for generating multiple luminescent colors (blue-green-white-yellow). The J-aggregated state of 1 forms a luminescent gel in THF and this luminescent property is retained even in the solid state.